Die next - Stone, Jonathan, 1956- (Grand Central Publishing, 2020)
"Zack cannot believe his luck when he learns that a man next to him at a coffee shop accidentally picked up the wrong phone. He's even more surprised when he's able to open the phone and discovers that his new phone-pal is actually a professional killer. Trapped in a high-stakes cat-and-mouse game with a highly trained assassin was definitely not how Zack planned to spend his day. Knowing Zack has access to incriminating evidence makes Zack the killer's next target, and with access to Zack's phone, the hitman's job just got a whole lot easier"--